2002
DOI: 10.1097/00000658-200203000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Groin Hernia With Synthetic Mesh

Abstract: The use of synthetic mesh substantially reduces the risk of hernia recurrence irrespective of placement method. Mesh repair appears to reduce the chance of persisting pain rather than increase it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…These results are comparable to results of many other studies [20] [21]. When comparing UHS with the classic Lichtenstein repair of inguinal hernia, many studies showed equivalent results for both techniques regarding intra and post-operative complications, length of hospital stay, duration of analgesics use, and time to return to usual activities [10] [11] [22]. Regarding operative time, some studies showed shorter operative time for UHS [20] [23]; other studies had longer operative time for UHS compared to Lichtenstein repair [24].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are comparable to results of many other studies [20] [21]. When comparing UHS with the classic Lichtenstein repair of inguinal hernia, many studies showed equivalent results for both techniques regarding intra and post-operative complications, length of hospital stay, duration of analgesics use, and time to return to usual activities [10] [11] [22]. Regarding operative time, some studies showed shorter operative time for UHS [20] [23]; other studies had longer operative time for UHS compared to Lichtenstein repair [24].…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, in the pre-peritoneal approach, the mesh is placed posteriorly in the pre-peritoneal space to cover Fruchaud myo-pectineal orifice completely [10] [11]. In 1997, Gilbert described his technique [4] that combined both the anterior and the posterior pre-peritoneal approach by the use of the Prolene Hernia System that gives the patient the advantages of both techniques with comparable short and long term results [12].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the numerous randomised trials and meta-analyses, procedures using a mesh have become the gold standard in the surgical repair of inguinal hernia [2, 53, 54]. Procedures using a mesh have reduced the rate of recurrence from 15% to less than 1% [55, 56].…”
Section: Surgical Site Infection: Costs and Consequencesmentioning
confidence: 99%
“…After two decades of mesh use, it is clear that this technique can help to reduce the manifestation of recurrences [5]. Furthermore, particularly in the case of a recurrence, the laparoscopic approach is faster than the open redo procedure and may have the advantage of reducing the incidence of postoperative chronic pain.…”
Section: Textiles In Surgerymentioning
confidence: 99%